Evaluasi Kualitas Citra Mamografi Metode Automatic Exposure Control (AEC) Menggunakan Normalized Anisotropic Quality Index (NAQI) - Ririn Septya Anggraini; Ni Larasati Kartika Sari; Idris Kusuma; Febria Anita (Universitas Nasional, 2022)
Mammography image is expected to have high image resolution quality so that the image is able to show microcalcifications as a sign of a malignant breast tumor with a size ranging from 0.1 mm. Automatic Exposure Control (AEC) is an image acquisition mode in mammography that is designed to strike a balance between patient dose and image quality by accommodating differences in breast size. This study aims to obtain the results of measuring mammographic image quality using Normalized Anisotropic Quality Index (NAQI), assessing the performance of AEC against variations in Compressed Breast Thicknes (CBT), density and Average Glandular Dose (AGD). This study using 20 mammographic images in AEC mode, Cranio Caudal (CC) projections. The data in the forms of CBT, breast density and AGD were also taken. In this study, the CBT range was 45-81 mm, the density range was 14-18%, the AGD range was 1.25-2.26 mGy with the patient's age ranged from 39-67 years and the compression pressure ranged from 20.0169-157.9111 N. Then the images are grouped based on CBT, density and AGD, to get the NAQI values. The results of NAQI values are e ues sults o(0.111-2). The highest NAQI value obtained on CBT images of 61 mm, density 14.64% and AGD 1.41 mGy.